Aplikasi Rekomendasi Tempat Makan berdasarkan Lokasi (Location Based Service) - Stefanie Natasha Tjia; Djoni Haryadi Setiabudi; Henry Novianus Palit (Jurnal Infra, 2020)
The ease and affordability of transportation causes many people totravel or travel to another area or city. Salty people will needinformation about where to eat. From the quality and quantity, sothe application is needed to fulfill the information.The application that will be created is to provide a recommendationfor Places to Eat based on the closest distance from the coordinatesdetected by GPS from the user's mobile phone. In addition, thisapplication provides information about places to eat such asmenus, locations and also provides rating of eating and eatingplaces, which is useful to help users take a decision.Based on the results of tests that have been done, the applicationcan read GPS and provide recommendations based on the closestdistance to the user. Users can provide detailed meal ratings anddining places that are useful to help in making decisions inchoosing where to eat.